Development of a low-level 39Ar calibration standard – Analysis by absolute gas counting measurements augmented with simulation. (August 2017) - Williams, R.M.; Aalseth, C.E.; Brandenberger, J.M.; Day, A.R.; Finn, E.; Fuller, E.S.; Hoppe, E.W.; Humble, P.H.; Keillor, M.E.; Mace, E.K.; Myers, A.W.; Overman, C.T.; et al.
Abstract: This paper describes the generation of 39 Ar, via reactor irradiation of potassium carbonate, followed by quantitative analysis (length-compensated proportional counting) to yield two calibration standards that are respectively 50 and 3 times atmospheric background levels. Measurements were performed in Pacific Northwest National Laboratory's shallow underground counting laboratory studying the effect of gas density on beta-transport; these results are compared with simulation. The total expanded uncertainty of the specific activity for the 50× 39 Ar in P10 standard is 3.6% (k=2). Highlights: 39 Ar is generated via reactor irradiation of potassium carbonate. Low-level standards are produced to assist in ground water age-dating studies. Quantification using length compensated proportional counting is performed. Wall- and threshold-effects are studied and discussed in terms of uncertainty.